Evaluation of Fluorine-18-Labeled α1(I)-N-Telopeptide Analogs as Substrate-Based Radiotracers for PET Imaging of Melanoma-Associated Lysyl Oxidase - Kuchar, Manuela; Neuber, Christin; Belter, Birgit; Bergmann, Ralf; Lenk, Jens; Wodtke, Robert; Kniess, Torsten; Steinbach, Jörg; Pietzsch, Jens; Löser, Reik (Frontiers in Chemistry, 2018)
Accumulating evidence suggests an unequivocal role of lysyl oxidases as key players of tumour progression and metastasis, which renders this enzyme family highly attractive for targeted non-invasive functional imaging of tumours. Considering their function in matrix remodelling, malignant melanoma appears as particularly interesting neoplasia in this respect. For the development of radiotracers that enable PET imaging of the melanoma-associated lysyl oxidase activity, substrates derived from the type I collagen alpha1 N-telopeptide were labelled with fluorine-18 using succinimidyl 4-[18F]fluorobenzoate ([18F]SFB) as prosthetic reagent. With regards to potential crosslinking to tumour-associated collagen in vivo, their interaction with triple-helical type I collagen was studied by SPR. A mouse model of human melanoma was established on the basis of the A375 cell line, for which the expression of the oncologically relevant lysyl oxidase isoforms LOX and LOXL2 was demonstrated in Western blot and immunohistochemical experiments. The radiopharmacological profiles of the peptidic radiotracers were evaluated in normal rats and A375 melanoma-bearing mice by ex vivo metabolite analysis, whole-body biodistribution studies and dynamic PET imaging. Out of three 18F-labelled telopeptide analogues, the one with the most favourable substrate properties has shown favourable tumour uptake and tumour-to-muscle ratio. Lysyl oxidase-mediated tumour uptake was proven by pharmacological inhibition using β-aminopropionitrile and by employing negative-control analogues of impeded or abolished targeting capability. The latter were obtained by substituting the lysine residue by ornithine and norleucine, respectively. Comparing the tumour uptake of the lysine-containing peptide with that of the non-functional analogues indicate the feasibility of lysyl oxidase imaging in melanoma using substrate-based radiotracers.